Chemical prospecting of Malaysian dipterocarpaceae from HSUiTM, Pahang, Malaysia - Wan Mohd Zain, Wan Zuraida; Ahmat, Norizan; Nawi, Liliwirianis; Jusoff, Kamaruzaman (IDOSI Publications, 2010)
A great majority of the Malaysian population relies on indigenous medicinal plants for treatment of diseases. The search for the plant constituents with potential activity for medicinal purpose can be performed successfully by chemical methods and, in combination with biological evaluation. However, pre selection of plants to be investigated is also one of the most important prerequisite. In HSUiTM, there are many plants that have not been evaluated for their potential medicinal value. This paper presents a brief review on resveratrol in dipterocarpaceae plants and their health benefits also presented.